Investigating the Relationship between Pre-service Social Studies Teachers Professional Knowledge and Motivational Orientation in Nigerian Universities - Aghahowa, Bernice Nefeye; Egharevba , John; Iyamu, Ede Sunday (Papanda Publisher, 2024)
This research examines the relationship between the professional knowledge and motivational orientation of prospective Social Studies educators in South-South Nigerian public universities. Employing a survey design, the study encompasses a population of 866 pre-service Social Studies teachers across state and federal universities within the South-South geopolitical zone. A sample of 446 participants was drawn from the population. Data collection involved an achievement test measuring content knowledge and pedagogical content knowledge, alongside a